Práce s empirickými daty: příručka pro studenty Bc. studia ČJL - Jan Chromý (Karolinum Press, 2014)
This book primarily servers as study material for the "Working with Empirical Data" class taught as part of a specialized module of the bachelor program of the Czech Language and Literature Program at the Faculty of Arts, Charles University in Prague. The book covers basic areas of the (primarily quantitative) empirical research focusing on language and its use, which makes it useful for anyone interested in this research field. The text is based on the explanation of empirical research terminology and approaches. Although the relatively limited scope only allows for a general presentation of some issues, references to other, supplementary sources allow readers to pursue this theme in detail, should they be interested.